The good wife of Bath : a (mostly) true story - Brooks, Karen (Australian author) (William Morrow, an imprint of HarperCollinsPublishers, 2022)
In 1364 England, one of literature's most unforgettable characters--Chaucer’s Wife of Bath--tells her story in her own words as she rises through society from a cast-off farm girl to a woman of fortune fighting to control her own life.